Nursing consultation for the diabetic in the family´s health program: - Nara Maria Costa Bezerra; Thereza Maria Magalhães Moreira; Sílvia Maria Nóbrega Therrien; Maria Irismar de Almeida (Rev Rene)
The diabetes is a globally incident chronic disease. The objective of this research was to describe the perception of the nurse as well as of the user about nursing consultation for the diabetic in the family's health program (PSF). The descriptive study was made through the application of questionnaires to eight nurses and of forms to 50 people of three health units who had diabetes. The results show that four of the interviewed people mentioned the consultation as na opportunity of a holistic viewing of the client and seven nurses detached difficulties in its implementation. As regards the clients, 45 couldn't inform the kind of diabetes they had, but everybody mentioned the need of going on a diet, 35 of taking care of their feet and 29 of practicing physical exercises. Twenty told they were not on a diet and 42 were not carrying out any physical activities. The nursing consultation was approved by 45 clients. As a conclusion the nursing consultation was considered as a contribution for the control of the diabetes for nurses and users, consisting in na opportunity of favoring the therapeutic compliance.